Factors Causing The Incident Of Malnutrition In Children In West Nusa Tenggara Province - Zahratul Hayati (Sean Institute, 2023)
Nutritional problems in children are one of the impacts of imbalances in health nutritional status in some developing countries. The Food and Agriculture Organization (FAO) reported that the number of malnourished children in the world in 2020 had reached 768 million people, an increase of 18.10% from the previous year, namely 650.30 million people. The aim of this research is to look at factors that can influence the incidence of malnutrition in West Nusa Tenggara Province based on previous research. The research method used in this research is literature review research which is reviewed systematically. The results of a review of research articles show that there are several factors that cause malnutrition in children in West Nusa Tenggara Province, namely economic status, educational status and parenting patterns.